Dissemination Dynamics of Receding Words: A Diachronic Case Study of Whom - Bohmann, Axel; Bohmann, Martin; Hinrichs, Lars (Frontiers in Artificial Intelligence, 2021)
We explore the relationship between word dissemination and frequency change for a rapidly receding feature, the relativizer whom. The success of newly emerging words has been shown to correlate with high dissemination scores. However, the reverse – a correlation of lower dissemination scores with receding features – has not been investigated. Based on two established and two newly developed measures of word dissemination – across texts, linguistic environments, registers, and topics – we show that a general correlation between dissemination and frequency does not obtain in the case of whom. Different dissemination measures diverge from each other and show internally variable developments. These can, however, be explained with reference to the specific sociolinguistic history of whom over the past 300 years. Our findings suggest that relationship between dissemination and word success is not static, but needs to be contextualized against different stages in individual words’ life-cycles. Our study demonstrates the applicability of large-scale, quantitative measures to qualitatively informed sociolinguistic research.